Effect of including corner point fluxes on the pin power reconstruction using nodal point flux scheme - Khoshahval, F.; Zolfaghari, A.; Minuchehr, H. (Annals of nuclear energy, 2014)
•Including corner fluxes improve pin power reconstruction.•The maximum errors in pin power reconstruction occur in the peripheral water region.•The errors are significantly less in the fuel region.•MSS predictions for corner pin flux are preferable. Although there have been well established transport based codes for core neutronics analysis, it is yet impractical to implement them in the real core treatment because their performance is not so great on ordinary server computers. For this reason, most of neutronics codes for core calculation are subject to two steps calculation procedure which consists of homogenized group constant generation and flux distribution generation which is the main concern of this work. This paper brings out a 2 dimensional nodal code based on point flux algorithm and implements two schemes for pin power reconstruction. In the first scheme, pin power reconstruction is obtained without considering corner point fluxes in the fuel assemblies but in the second method corner fluxes are included to assess their effect on pin power reconstruction. To obtain corner point fluxes, Smith’s procedure and the method of successive smoothing are used. Improvement in pin power reconstruction by including fuel assembly corner fluxes is illustrated in this paper and assessed by Monte Carlo simulation.